2021
DOI: 10.3390/antiox10050699
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Broiler Chickens with Grape Seed and Skin Meals to Enhance α- and γ-Tocopherol Content and Meat Oxidative Stability

Abstract: Grape seeds (GS) and grape skins (GK) are natural sources of polyphenols with featured antioxidant capacity. An experiment was conducted to investigate the effect of these polyphenol sources in diets formulated to contain the same total extractable grape polyphenol content on growth performance, protein and extractable polyphenol digestibility, plasma and meat α- and γ-tocopherol and thigh meat oxidation in broiler chickens. Five experimental diets were formulated: control, control + vitamin E (200 mg/kg), 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 52 publications
6
23
0
3
Order By: Relevance
“…The obtained results indicate an improvement in breast meat oxidative stability. In agreement with our study, the supplementation of grape seeds and skin meal in broilers’ diet significantly decreased the TBARS levels of thigh meat, indicating the synergetic action of γ- and a-tocopherols for stabilizing lipid peroxidation [ 66 ]. Similarly, the inclusion of green tea extract rich in catechins, epigallocatechin-3-gallate, and caffeine in quail diet decreased the MDA concentration in liver and blood plasma [ 67 ].…”
Section: Discussionsupporting
confidence: 90%
“…The obtained results indicate an improvement in breast meat oxidative stability. In agreement with our study, the supplementation of grape seeds and skin meal in broilers’ diet significantly decreased the TBARS levels of thigh meat, indicating the synergetic action of γ- and a-tocopherols for stabilizing lipid peroxidation [ 66 ]. Similarly, the inclusion of green tea extract rich in catechins, epigallocatechin-3-gallate, and caffeine in quail diet decreased the MDA concentration in liver and blood plasma [ 67 ].…”
Section: Discussionsupporting
confidence: 90%
“…The first are antioxidants that interrupt radical reactions by donating hydrogen atoms or electrons to radicals, which leads to the formation of compounds with greater stability. Such compounds include: tocopherols [6,7], phenols [8], hydroquinones [9]. The second group includes substances whose action is synergistic.…”
Section: Introductionmentioning
confidence: 99%
“…Before grinding, seeds were subjected to an expeller oil extraction process. The proximate composition and the characterization of phenolic compounds of GS and GK can be found in the previous study of Romero et al [ 11 ]. Briefly, GS and GK contained, respectively, 19.6 and 16.3 g/100 g dry matter (DM) of crude protein (CP); 25.4 and 14.5 g/100 g DM of crude fibre; 5062 and 4500 cal/g of gross energy; 7.93 and 2.35 g of TEP (gallic acid equivalents/100 g DM) and 1.15 and 1.24 of condensed tannins (g cyanidin/100 g DM).…”
Section: Methodsmentioning
confidence: 99%
“…In monogastric animals, it has been demonstrated that the dietary inclusion of grape byproducts can affect intestinal barrier and microbial ecosystem [ 9 , 10 ]. Additionally, grape phenolic compounds have also shown to be bioavailable and effective in reaching target tissues, which, among other effects, has made possible increases in α- and γ-tocopherol contents in plasma and meat and a reduction of meat lipid oxidation in chickens fed grape byproducts [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation